Ondřej Pilný, ed. Irish Theatre & Central Europe. Special issue of Litteraria Pragensia – Studies in Literature and Culture 25.50 (December 2015). 140 pp. - Csikai, Zsuzsa (FOCUS: Papers in English Literary and Cultural Studies, 2016)
The special issue of Litteraria Pragensia, titled Irish Theatre & Central Europe, edited by Ondřej Pilný, examines the presence of Irish drama on the stages of Continental Europe in the twentieth and twenty-first centuries. The volume, exploring this mostly uncharted territory, gathers together scholars of Irish literature as well as theatre practitioners, whose essays shed light on the intriguing ways in which Irish drama has been received, interpreted, and transformed in various theatre productions in Central Europe. Here, outside the “comfort zone” of English-speaking countries, Irish drama is offered to audiences in translation, and where a further challenge for both theatre practitioners and audiences is posed by the receiving culture’s relative unfamiliarity with the phenomenon of Irish theatre as a distinct tradition well-established within the Anglophone world.